A rare AAT variant presenting in a COPD patient: Q0 amersfoort mutation - Seda Tural Önür; Kardelen Karaca Şenkal (Respiratory Medicine Case Reports, 2024)
Introduction: Alpha-1 antitrypsin (AAT) deficiency, characterized by reduced synthesis of a serine protease inhibitor in liver cells, has been recognized to contribute to the development of emphysema and liver disease. Additional clinical manifestations encompassing respiratory disorders and dermatological issues have also been documented. Case: A 56-year-old male patient presented with dyspnea. Despite being a non-smoker, he had a diagnosis of chronic obstructive pulmonary disease (COPD) five years ago. Utilizing inhaled corticosteroids (ICSs) - long-acting β2-agonists (LABAs)- long-acting muscarinic antagonists (LAMAs) inhalers, the patient's medical treatment had ceased for the past four months due to inhaler depletion. High-resolution thoracic computed tomography unveiled bilateral emphysematous regions, predominantly located in the lower pulmonary lobes. In light of the absence of smoking history, the suspicion of AAT deficiency was raised, prompting the assessment of serum AAT levels. Subsequent analysis indicated diminished AAT levels, prompting the collection of a dried blood sample for genetic evaluation. Genomic DNA amplification was performed using polymerase chain reaction (PCR), succeeded by allele-specific hybridization via Luminex XMAP Technology. This analysis disclosed a Q0amersfoort (Exon 2 Y160TAC > Ter TAG) (+/+) variant linked with AAT deficiency, originating from a frame-shift mutation that triggers a null (Q0amersfoort) stop codon. Conclusion: The presentation of COPD-related emphysema in a non-smoker underscores the necessity to consider AAT deficiency in the differential diagnosis.